2020
DOI: 10.25796/bdd.v3i4.59643
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic SARS-CoV2 infections in patients treated in France by hemodialysis in an establishment, or at home or by peritoneal dialysis: Data from the REIN and RDPLF registries

Abstract: In France all patients treated with dialysis are registered in the REIN registry  (Epidemiology and Information Network in Nephrology) ; in addition  the RDPLF (French Language Peritoneal Dialysis Registry) monitors patients treated at home in French-speaking regions and countries. Asymptomatic patients with a positive SARS-CoV2 test were excluded :  the study focused only on patients with symptomatic COVID-19 disease. Data from REIN and RDPLF were used. In total, 3,541 patients were declared symptomatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
1
0
1
Order By: Relevance
“…40 These trends were confirmed by studies from the United Kingdom, Canada, Spain and France. [41][42][43] In the United Kingdom, the mortality rate from Covid-19 was more than twice among those who received HD in-centres compared with those on home-based dialysis during the first wave of the pandemic. 44 The ERA-EDTA Registry reported that the mortality in dialysis patients and kidney transplant recipients infected with Covid-19 across Europe was 20% on average, though it reached 30% in Spain, Switzerland and Netherlands.…”
Section: Covid-19 Infectionmentioning
confidence: 99%
“…40 These trends were confirmed by studies from the United Kingdom, Canada, Spain and France. [41][42][43] In the United Kingdom, the mortality rate from Covid-19 was more than twice among those who received HD in-centres compared with those on home-based dialysis during the first wave of the pandemic. 44 The ERA-EDTA Registry reported that the mortality in dialysis patients and kidney transplant recipients infected with Covid-19 across Europe was 20% on average, though it reached 30% in Spain, Switzerland and Netherlands.…”
Section: Covid-19 Infectionmentioning
confidence: 99%
“…La Figure 2 moment de la rédaction de cet article, l'Agence de Biomédecine estimait que 16 % des patients dialysés, toutes méthodes confondues, auraient présenté une infection à SARS-Cov2 et que 20% des décès seraient liés à ce virus [7]. En ne considérant que les patients symptomatiques (donc en excluant ceux qui avaient un test positif sans signe clinique), nous avons trouvé récemment, dans une étude commune des deux registres REIN et RDPLF, un taux de 8 % de patients symptomatiques (donc en excluant ceux qui avaient une recherche de Covid sans signe clinique) chez les patients traités dans une unité de dialyse, alors que ceux traités [8] à domicile par DP ou hémodialyse à domicile étaient symptomatiques dans 4,9 % des cas au cours des neuf premiers mois de l'année 2020 [8]. La volonté des néphrologues de limiter les contacts dans les transports ou les établissements de soins a favorisé en France la constitution d'un réseau de développement de l'hémodialyse à domicile, mais ce dernier se heurte à des contraintes organisationnelles et financières [9].…”
Section: Variation De L'incidenceunclassified